Design and fabrication a machine for chopping palm bunches for compost - Yusuf, Ilyas; Hidayat, T Rian; Darmein, Darmein (Journal of Mechanical Engineering and Fabrication, 2025)
In the manual shredding process, the capacity is 50-70 kg/hour. Therefore, a crusher machine is needed to increase the capacity. The results of crushing the oil palm bunches can be used as compost. In this design, the cutting blade is designed with a larger number of cutting blades to accelerate the production of oil palm bunches so that it can operate optimally and does not require excessive power to move the tool because the tool designed will be driven using a gasoline engine and by adding cutting blades, the production capacity will increase. Design is one of the important things in making a program. The purpose of the design is to provide a clear and complete picture to the programmers and engineers involved. The design must be useful and easy to understand so that it is easy to use. Design is a process to define something that will be experienced in the process. The results of the machine test were able to produce a crushing capacity with a length of 3 - 14 cm, a width of 3 - 20 mm and ± 8.5 kg in one minute. The following is a systematic calculation of machine capacity: 1 minute = 8.5 kg per second 1 hour = 8.5 kg x 60 minutes = 510 kg/hour.